Outcome of Early Excision versus Delayed Excision and Grafting in Burn Less than Twenty Percent Body Surface Area (Journal of Nobel Medical College, 2023)
Background: Burn injuries are a significant public health concern associated with high morbidity and mortality. Surgical interventions, including early excision and grafting or delayed excision and grafting are crucial for deep burns. This study compares graft take, number of procedures, duration of stay, and burn wound infections between early excision and grafting and delayed excision and grafting groups.Materials and Methods: A comparative study was conducted at a burn referral center from January 1st to March 31st, 2020. Eighty-six patients (43 in each group) with deep burns covering 10-20% TBSA were included. Early excision and grafting and delayed excision and grafting groups were determined by the timing of the first operation (within or beyond 7 days post-injury). Parameters compared included graft take, number of grafting procedures, duration of stay, and graft site infection.Results: Both groups had a mean age of 42.6 years, with predominantly female populations. The mean total body surface area % of burn area was 15%. Early excision and grafting and delayed excision and grafting groups showed comparable outcomes in graft take (90.6% vs. 88.16%), mean duration of hospital stay (16.72 vs. 16.53 days), number of surgical procedures (1.3 vs. 1.4), and graft site infection (23.3% vs. 30.2%).ConclusionGraft take, duration of hospital stay, number of surgical procedures, and graft site infections were comparable in Early excision and grafting and delayed excision and grafting groups for burns covering less than twenty percent body surface area. Delay in excision and grafting did not significantly impact outcomes in smaller burns, providing valuable insights for managing delayed burn presentations.